Dossier: Materia medica and pharmacy. From medicinal virtues to the active principles of plants - Ferraz, Márcia H.M.; Aceves Pastrana, Patricia; Alfonso-Goldfarb, Ana M. (Circumscribere International Journal for the History of Science, 2015)
The papers included in the present dossier were selected for a symposium held at the 24th International Congress of History of Science, Technology and Science (ICHSTM), Manchester, 2013. They deal with different aspects of the transition from the traditional notions of simple drugs and material principles to the modern idea of active principles, as reflected in the specialized literature, namely, works on materia media, pharmacy, pharmacopoeia, pharmacology and therapeutics.